A Polyclonal Immune Function Assay Allows Dose-Dependent Characterization of Immunosuppressive Drug Effects but Has Limited Clinical Utility for Predicting Infection on an Individual Basis - Marx, Stefanie; Adam, Claudia; Mihm, Janine; Weyrich, Michael; Sester, Urban; Sester, Martina (Frontiers in Immunology, 2020)
Dosage of immunosuppressive drugs after transplantation critically determines rejection and infection episodes. In this study, a global immune function assay was characterized among controls, dialysis-patients, and transplant-recipients to evaluate its utility for pharmacodynamic monitoring of immunosuppressive drugs and for predicting infections. Whole-blood samples were stimulated with anti-CD3/toll-like-receptor (TLR7/8)-agonist in the presence or absence of drugs and IFN-γ secretion was measured by ELISA. Additional stimulation-induced cytokines were characterized among T-, B-, and NK-cells using flow-cytometry. Cytokine-secretion was dominated by IFN-γ, and mainly observed in CD4, CD8 and NK-cells. Intra-assay variability was low (CV=10.4±6.2%), whereas variability over time was high, even in the absence of clinical events (CV=65.0±35.7%). Cyclosporine A, tacrolimus and steroids dose-dependently inhibited IFN-γ secretion, and reactivity was further reduced when calcineurin inhibitors were combined with steroids. Moreover, IFN-γ levels significantly differed between controls, dialysis patients, and transplant-recipients, with lowest IFN-γ levels early after transplantation (p<0.001). However, a single test had limited ability to predict infectious episodes. In conclusion, the assay may have potential for basic pharmacodynamic characterization of immunosuppressive drugs and their combinations, and for assessing loss of global immunocompetence after transplantation, but its application to guide drug-dosing and to predict infectious on an individual basis is limited.